POLA ASUH ANAK DALAM KELUARGA PETANI DI DOMLOLI KABUPATEN ALOR - Raspa Laa (Universitas Muhammadiyah Ponorogo, 2018)
This research aims to describe the form of parenting performed by a parent with the back work as a farmer in Domloli Alor District. To know this condition, the problem formulation used is 1) How to take care of child pattern in farmer family in Domloli of Alor Regency 2) what are the factors that cause the weakness of child care pattern in farmer family in Domloli of Alor Regency and 3) how is the impact caused by the weakness of parenting for the parents of farmers in Domloli Alor District. The research method used is qualitative ethnomethodology with data taking using 1) interview and 2) observation method. The result is this research, there are three forms of parents parenting such as the parents who does not concern with children education, they does not have enough time for gathering with their children and no effective communication between them. The cause of the emergence of this parenting pattern is a poor parent's understanding of children's education, as well as weak parents education. This will have an impact on the loss of parental responsibility for the child.